2023
DOI: 10.1002/hsr2.1145
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin effects on chronic obstructive pulmonary disease: A systematic review

Abstract: Introduction Chronic obstructive pulmonary disease (COPD) is a common disease of the lungs known as the third reason for death worldwide. Frequent COPD exacerbations compel health care workers to apply interventions that are not adverse effect free. Accordingly, adding or replacing Curcumin, a natural meal flavoring, may indicate advantages in this era by its antiproliferative and anti‐inflammatory effects. Methods The PRISMA checklist was employed for the systematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Furthermore, BJG is mainly applied in clinical practice to treat COPD, and the vicious cycle of inflammation and oxidative stress is a prominent manifestation in COPD patients (Safari et al, 2023). The 10 blood components tested in this study exhibited anti‐inflammatory, antioxidant, analgesic, and other biological activities to varying degrees.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, BJG is mainly applied in clinical practice to treat COPD, and the vicious cycle of inflammation and oxidative stress is a prominent manifestation in COPD patients (Safari et al, 2023). The 10 blood components tested in this study exhibited anti‐inflammatory, antioxidant, analgesic, and other biological activities to varying degrees.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, BJG is mainly applied in clinical practice to treat COPD, and the vicious cycle of inflammation and oxidative stress is a prominent manifestation in COPD patients (Safari et al, 2023).…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
“…Studies have revealed that curcumin, a dietary polyphenol derived from the turmeric rhizome, offers therapeutic advantages in COPD by suppressing nuclear factor kappa B (NF-κB) [ 11 ]. Curcumin’s modulatory effects on oxidative stress, cell viability, and gene expression may benefit COPD therapy [ 12 ]. Due to its chemical contains, curcumin possesses a strong antioxidant potential that is almost three times greater than that of vitamin C and more than 1.5 times greater than that of vitamin E [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many systemic manifestations of COPD are believed to be exacerbated by systemic inflammation, including elevated IL-6 levels. Various animal and cellular studies have shown the promising effect of curcumin on COPD, and their results have been discussed in a systematic review study (Safari et al, 2023). In the only clinical trial study, in this issue, Funamoto et al (2016) showed that the administration of curcumin significantly reduced the level of atherosclerotic low-density lipoprotein compared to the control group in non-smoker patients with mild COPD.…”
mentioning
confidence: 99%